Pengembangan Model Pengambilan Keputusan Multi Kriteria dalam menentukan Trade-Off Tujuan Berkonflik menggunakan Global Criterion Method - S. Sutrisno; Dyah Rachmawati Lucitasari (OPSI, 2019)
Decision making by company management is mostly multi-criteria decision making. Multi-criteria corporate decision making is characterized by having to make decisions on several corporate objectives that are mutually contradictory. Service companies generally want to maximize customer satisfaction and minimize company operating costs. Customer satisfaction can be maximized, by implementing programs that are expected to maximize the level of customer satisfaction. Implementation of these programs will increase the company's operational costs, which in turn can reduce company profits. The company's goal to increase customer satisfaction results in increased operational costs, so that it is contradictory to the second corporate goal of minimizing company operating costs, which is a multi-criteria decision making problem.Trade-offs are sought from two contradictory service company objectives, namely maximizing customer satisfaction and minimizing company operating costs, firstly, a multi-criteria decision making model will be developed. The decision-making model developed is a mathematical model consisting of two contradictory objective function functions, namely the maximization of the level of customer satisfaction and the minimization of the company's operating costs, as well as a limitation which is a mathematical translation of the things that limit the achievement of these two company goals. After a mathematical model of multi-criteria decision making is formed, the next step is to look for trade-offs from the two company's goals using the global criterion method.